DESIGN OF AN OPTIMAL AUTOMATED PROCESS CONTROL SYSTEM FOR A HYDROPONIC DEVICE WITH A REMOTE MONITORING FUNCTION - Gulmurodova Go’zal Qobiljon qizi (Bright Mind Publishing, 2026)
This article investigates the design of an optimal automated process control system for a hydroponic installation equipped with a remote monitoring function. The main objective of the study is to develop an effective control solution that enables real-time monitoring and automatic regulation of environmental parameters in hydroponic systems in order to enhance process stability and productivity. The proposed system focuses on the continuous control of key parameters such as pH level, electrical conductivity (EC), temperature, humidity, and light intensity, which play a critical role in plant growth and development. An automated control structure based on sensors, actuators, and feedback control algorithms is presented. In addition, an IoT-based remote monitoring platform is integrated into the system, allowing users to observe system status, collect data, and perform analytical evaluations remotely. The control strategy is designed using a feedback-based optimal control approach, and its applicability to hydroponic processes is theoretically and experimentally justified. Experimental results demonstrate that the proposed automated control and remote monitoring system ensures stable operation of the hydroponic process, improves resource efficiency, and contributes to increased crop productivity. The findings of this study have significant scientific and practical value for the development of smart agriculture technologies and the automation of modern hydroponic systems.
Keywords: Hydroponic system; automated control system; remote monitoring; Internet of Things (IoT); optimal control; sensor-based monitoring; smart agriculture.